Why wear a seat belt? I’m going to die anyway: Young Arab men’s rationales for deadly driving behaviors - Susan Dun (19807227) (2015)
Safe driving campaigns in Qatar are in their infancy. The first campaigns were fear appeals that typically involved pictures of vehicles that had been smashed almost beyond recognition in accidents posted on signs around the capital city, Doha. A second generation of campaigns has recently been developed that are also fear appeal based, but feature more sophisticated messaging and visuals than the first group did. While laudable in their goals, both set of campaigns are not based on either a theoretical framework or research on the target audience. Evaluation research on the specific campaigns has not been conducted making assessment of message efficacy difficult. Even if the campaigns have had some effectiveness, 18-25 year old Qatari men, our target audience, continue to be the highest risk group, involved in a disproportionate number of MVCs, suggesting the campaigns are not working for this cohort at all. One of the common reasons message campaigns fail to have the intended effect is the lack of correspondence between the message content, form and design and the audience’s attitudes and beliefs (Yzer, 2012). The stronger the match is between the message and the audience, the higher the likelihood of persuasion. Creating a message that is closely tailored an audience requires an understanding of the way they think and are likely to respond to messages. We conducted focus group discussions with 18-25 year old Qatari male drivers to discover their driving attitudes and behaviors to provide guidance for tailored message campaigns designed to change their attitudes and behavior. We discovered that the perceived capability of actually changing one’s behavior is seriously impeded by a couple of characteristics our respondents shared and that they typically engage in quite risky driving behaviors. The two characteristics our respondents reported are fatalism and high sensation seeking. Fatalism is a belief that what happens to a person is not as a result from their own behaviors but rather is caused by an entity higher that them, typically God, but non-religious people can nonetheless still have high levels of fatalism (Shen & Condit, 2012). A high level of fatalism presents a challenge to message campaigns because the message recipients, who believe they do not have control over their own fate, may reject the desired behavioral change. High sensation seeking increases the resistance to a more negative attitude toward reckless driving – because it is rewarded by both the psychological pleasure derived from dangerous actions and by young men’s peers. Driving at excessive speeds and refusing to wear seat belts are some of the high-risk behaviors our respondents reported. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.79